Analisis Dampak Digitalisasi pada Bisnis Logistik di Era Revolusi 4.0 - Erliyana, Sulida; Pambudi, M. Aji Luhur (Majalah Ilmiah Gema Maritim, 2024)
In the era of the Industrial Revolution 4.0, digitalization has changed the logistics business significantly. Impact analysis is revealed through improved operational efficiency, better supply chain visibility, and innovation in services. The implementation of technologies such as the Internet of Things (IoT), big data analytics, and artificial intelligence has enabled logistics companies to optimize inventory management, track shipments in real time, and predict supply needs. The purpose of this research is to assist companies in the logistics industry in managing inventory, processing orders, monitoring supplier status, and various other operational activities. The writing method used is qualitative with a literature review approach. The data used in the study are secondary data collected from various articles. Therefore, it is expected that the adoption of digital platforms and smart transportation management systems will facilitate collaboration between stakeholders in the supply chain, increase transparency, and reduce logistics costs. While there are substantial benefits, challenges related to data security and technology integration also need to be addressed. Therefore, the analysis of the impact of digitalization on the logistics business in the era of Revolution 4.0 reflects a fundamental shift towards more efficient operations and adaptation to evolving market demands.